ANALYSIS OF BUDGET DEFICIT AND ITS PROBLEMS IN LITHUANIA - F. Jaseviciene; E. Rudzionyte (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Budget deficit is one of the most important parts of macroeconomics. Since 1990, the government of the Lithuanian Republic has been faced with problems in balancing the budget deficit; most of the years, the country’s budget was deficit with the lack of incoming money flow. The budget deficit value in Lithuania has been a significant theme since 2004, when Lithuania became part of the European Union, and one of the liabilities was to insure the litas replacement with euro currency and the budget deficit was one of the Maastricht’s criteria. Also it is very important to maintain effective management of public finances. The government is responsible for managing the country’s budget in respect to various economical parameters, for example, GDP, inflation rate, unemployment rate, etc., in order to plan income level and distribute it to the relevant economic areas. Also, the budget deficit’s problems are revealed in this article.